2011
DOI: 10.1002/pds.2225
|View full text |Cite
|
Sign up to set email alerts
|

Use and costs of oral anticancer agents in the Netherlands in the period 2000–2008

Abstract: The increased use of oral anticancer agents is mainly due to the frequent prescription of capecitabine. The increased costs are caused by the registration of a variety of TKIs, in particular imatinib. The costs of new agents with an orphan drug status are very high as compared with those of capecitabine, a newer agent for which there are alternative treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Information on Oral Anticancer Agent Use C. C. L. M. Boons et al (Table 4). 1 Variables were dichotomized into most adverse quartile versus the other three quartiles (reference category). 2 Only patients on treatment (n = 130) were included in the regression analyses because quality of life was not assessed in patients off treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on Oral Anticancer Agent Use C. C. L. M. Boons et al (Table 4). 1 Variables were dichotomized into most adverse quartile versus the other three quartiles (reference category). 2 Only patients on treatment (n = 130) were included in the regression analyses because quality of life was not assessed in patients off treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Significant relations are shown in bold (P < 0.05). Abbreviations: OACA, oral anticancer agent; EORTC QLQ-C30, European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30; Brief IPQ, Brief Illness Perception Questionnaire; BMQ-Specific, Beliefs about Medicines Questionnaire Specific; OR, odds ratio; 95% CI, 95% confidence interval 1. Variables were dichotomized into most adverse quartile versus the other three quartiles (reference category) 2.…”
mentioning
confidence: 99%
“…The study showed that the cost per member per month (PMPM) experienced a nearly threefold increase from 2002 to 2006 for small, self-insured employers. Timmers et al [14] examined the medication cost of oral anticancer agents in The Netherlands. They also found a rapid increase in the use and costs of oral anticancer drugs, reporting a 50-fold increase in the costs of oral anticancer agents from 2000 to 2008 in The Netherlands.…”
Section: Non-drug-specific Studiesmentioning
confidence: 99%
“…The potentially serious cardiac side effects and cost of the treatment cannot be overlooked. A study conducted in the Netherlands analyzed the use and costs of oral anticancer agents between 2000 and 2008 and showed a 50-fold rise in costs of oral anticancer agents between 2000 and 2008; 67% of this rise was attributable to tyrosine kinase inhibitors (TKIs) 43. One of the most effective tyrosine kinase inhibitors, imatinib, has been evaluated in many pharmacoeconomic studies.…”
Section: The Ret Vegf-r and Egf-r Pathways In Mtcmentioning
confidence: 99%